771FUCS National Meeting of Colombian Health Research Seedbeds: our history 2004-2019. (2nd September 2021) - Castro, Carlos; Segura, Omar; Vivas, Laura
Abstract: Background: Comparative history applied to health education may be a tool to understand institutional key processes within our national health research evolution. In Colombia, first groups of undergraduates interested in research emerged in 1996, being called seedbeds. Universitary Foundation of Health Sciences (FUCS) developed its own seedbeds and created a National Meeting (NM) to join others as network. Objective here is to describe its evolution and perspectives along a 15-year timespan (2004-2019). Methods: Ethically approved qualitative hermeneutic-interpretative research using content analysis, compared history and interviews to key figures. Data came from digital files with FUCS policies (statutes, education plans and rules), FUCS High Council meetings acts and audiovisual material directly pertaining the NM; files were condensed using Endnote X9 and NVivo 12 to generate categories, benchmarks and timeline. Results: Three stages emerged: a) conception (2004-2009), seedbed was an external construct adopted by FUCS since formative research was embedded in its teaching activities; b) blooming (2010-2014), FUCS offices and areas participated in developing regulations and giving administrative/financial support, 19 seedbeds in 4 faculties were created, and first two NMs were advertised and executed, c) growth (2015-onwards) devoted to "maintenance & consolidation", with three events, country-wide participants from 57 universities and 370 research projects exhibited (2019). Conclusions: The NM reflect FUCS institutional development and progress in teaching and promoting research through organized, dynamic and productive undergraduate research seedbeds. Key messages: In Colombia, undergraduate seedbeds are promoted as paramount educational activity; in this endeavour, FUCS national meetings have become centre-piece after 15 years.